New insights into hypothalamic neurogenesis disruption after acute and intense stress: implications for microglia and inflammation - Infantes-López, María Inmaculada; Nieto-Quero, Andrea; Chaves-Peña, Patricia; Zambrana-Infantes, Emma; Cifuentes, Manuel; Márquez, Javier; Pedraza, Carmen; Pérez-Martín, Margarita (Frontiers in Neuroscience, 2023)
In recent years, the hypothalamus has emerged as a new neurogenic area, capable of generating new neurons after development. Neurogenesis-dependent neuroplasticity seems to be critical to continuously adapt to internal and environmental changes. Stress is a potent environmental factor that can produce potent and enduring effects on brain structure and function. Acute and chronic stress is known to cause alterations in neurogenesis and microglia in classical adult neurogenic regions such as the hippocampus. The hypothalamus is one of the major brain regions implicated in homeostatic stress and emotional stress systems, but little is known about the effect of stress on the hypothalamus. Here, we studied the impact of acute and intense stress (water immersion and restrain stress, WIRS), which may be considered as an inducer of an animal model of posttraumatic stress disorder, on neurogenesis and neuroinflammation in the hypothalamus of adult male mice, focusing on three nuclei: PVN, VMN and ARC, and also in the periventricular area. Our data revealed that a unique stressor was sufficient to provoke a significant impact on hypothalamic neurogenesis by inducing a reduction in the proliferation and number of immature neurons identified as DCX+ cells. These differences were accompanied by marked microglial activation in the VMN and ARC, together with a concomitant increase in IL-6 levels, indicating that WIRS induced an inflammatory response. To investigate the possible molecular mechanisms responsible for neuroplastic and inflammatory changes, we tried to identify proteomic changes. The data revealed that WIRS induced changes in the hypothalamic proteome, modifying the abundance of three and four proteins after 1 h or 24 h of stress application, respectively. These changes were also accompanied by slight changes in the weight and food intake of the animals. These results are the first to show that even a short-term environmental stimulus such as acute and intense stress can have neuroplastic, inflammatory, functional and metabolic consequences on the adult hypothalamus.